The Philosophy of Waḥdah Al-Wujūd in the Waḥdah Al-Wujūd Fī Bayān Al-Ma‘Rifah Min Kull Bayān Al-Muḥaqqiqīn Manuscript: A Study of Nusantara Sufi Traditions - Herdiansyah, Pradibyo; Azizah, Amiroh Nichayatun Munir; Djuaeni, M Napis; Syauqi Nafis, Andi Ahmad; Ulwan, Ahmad Hashif (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
This study examines the philosophical construction of Waḥdah al-Wujūd in the manuscript Waḥdah al-Wujūd fī Bayān al-Ma‘rifah min Kull Bayān al-Muḥaqqiqīn attributed to Muḥammad Makkī, a text that has received little scholarly attention despite its relevance to the development of nineteenth‑century Nusantara Sufi thought. Existing research on Wujūdiyyah in the archipelago has focused primarily on seventeenth‑ century figures such as Hamzah Fansuri and Abdurrauf Singkel, leaving a gap in understanding how later intellectual networks, particularly in Buton, adapted and transformed these metaphysical ideas. This study aims to fill that gap by analyzing the manuscript’s ontological framework and its contribution to the local articulation of Sufi philosophy. The research employs qualitative content analysis using primary data from the DREAMSEA digital manuscript DS 0010 00100, supported by comparative readings of Fansuri’s Sharab al-‘Āshiqīn and Singkel’s Tanbīh al-Māshī. Philological methods, including transcription, textual description, and thematic coding, were used to identify key metaphysical concepts. The findings show three major points. First, Makkī introduces a distinctive “shadow ontology” that maps divine manifestation onto the human microcosm. Second, he offers a theological distinction between Allāh and Ilāh that reframes debates on transcendence and immanence. Third, the manuscript demonstrates a reconciliatory form of Wujūdiyyah that integrates Fansuri’s metaphysics with Singkel’s cautionary theological stance. These insights highlight the manuscript’s role in shaping Butonese Sufi discourse and expanding the intellectual genealogy of Wujūdiyyah in the region. The study concludes that Muḥammad Makkī’s work represents a significant yet overlooked link in the evolution of Nusantara philosophical Sufism.